2015
DOI: 10.1039/c5cp02799c
|View full text |Cite
|
Sign up to set email alerts
|

Two phosphonium ionic liquids with high Li+ transport number

Abstract: This work presents the physicochemical characterization of two ionic liquids (ILs) with small phosphonium cations, triethylpenthylphosphonium bis(trifluoromethanesulfonyl)imide ([P2225][Tf2N]) and (2-methoxyethyl)trimethylphosphonium bis(trifluoromethanesulfonyl)imide ([P222(201)][Tf2N]), and their mixtures with Li(+). Properties such as the electrochemical window, density, viscosity and ionic conductivity are presented. The diffusion coefficient was obtained using two different techniques, PGSE-NMR and Li ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
45
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 61 publications
5
45
1
Order By: Relevance
“…Quaternary phosphonium-based ionic liquids (ILs) and their solid state analogs, organic ionic plastic crystals (OIPCs), have been developing rapidly in recent years as a result of many excellent properties being discovered and applied in a number of fields, such as lubricants, phase transfer catalysts, electrochemical media, optical materials, and CO 2 capture, to name a few. [1][2][3][4][5][6][7][8] As a relatively new class of ILs, their application in electrochemical devices, including rechargeable lithium and sodium batteries, has received particular attention of late.…”
Section: Introductionmentioning
confidence: 99%
“…Quaternary phosphonium-based ionic liquids (ILs) and their solid state analogs, organic ionic plastic crystals (OIPCs), have been developing rapidly in recent years as a result of many excellent properties being discovered and applied in a number of fields, such as lubricants, phase transfer catalysts, electrochemical media, optical materials, and CO 2 capture, to name a few. [1][2][3][4][5][6][7][8] As a relatively new class of ILs, their application in electrochemical devices, including rechargeable lithium and sodium batteries, has received particular attention of late.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The structure of these components and their degree of coordination have substantial influence over the physical properties of ILs, with the nature and relative sizes of the ions being known to strongly influence viscosity. 8,17,18 This in turn affects ionic conductivity, which is a crucial parameter in the design of EDLCs as it has a profound influence on the equivalent series resistance (ESR) of the cells. For example, it is known that ILs containing the bis(trifluoromethanesulfonyl) imide ([Tf 2 N]) anion exhibit relatively low viscosities and wide electrochemical stability windows (ESWs).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Martins et al have calculated the lithium transference number in phosphonium-based ionic liquids using both NMR and electrochemical methods and have found that the values calculated from the electrochemical method are 2-3 fold larger than the values calculated from the NMR method. 50 These authors have explained that NMR method underestimates the diffusion coefficient of charged species because it considers all the species and aggregates between lithium cation and the anion that are larger than the small charged Li + cation. Thus, their low diffusion coefficients decrease the overall diffusion coefficient and transference number of Li + cation.…”
mentioning
confidence: 99%